2008
DOI: 10.1007/s11284-008-0535-8
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic response to dynamic changes of light and air humidity in two moss species from the Tibetan Plateau

Abstract: Bryophytes are widely distributed in alpine meadow and wetlands on the Tibetan Plateau, where light intensity and air moisture are highly variable in time. To address how bryophytes respond to their light and moisture environments, we examined dynamic photosynthesis in two moss species, Distichium inclinatum common in meadow, and Encalypta alpine frequently found in wetland. Photosynthetic induction response was faster in the two moss species than in most vascular species. In both species the 90% induction tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 86 publications
2
15
1
Order By: Relevance
“…Our experiments confirmed and extended the findings of Cui et al (2009), that induction times of bryophyte photosynthesis are considerably shorter compared to the published values measured in tracheophytes ( Figure 4). Photosynthetic induction time IT50 (50% of maximum photosynthesis) in tracheophytes strongly correlates with the initial stomatal conductance (Gsi) before the induction (Allen & Pearcy, 2000).…”
Section: Induction O F Photosynthesis In Bryophytes Us Trocheophytessupporting
confidence: 92%
See 1 more Smart Citation
“…Our experiments confirmed and extended the findings of Cui et al (2009), that induction times of bryophyte photosynthesis are considerably shorter compared to the published values measured in tracheophytes ( Figure 4). Photosynthetic induction time IT50 (50% of maximum photosynthesis) in tracheophytes strongly correlates with the initial stomatal conductance (Gsi) before the induction (Allen & Pearcy, 2000).…”
Section: Induction O F Photosynthesis In Bryophytes Us Trocheophytessupporting
confidence: 92%
“…Although there is a discussion about photosynthetic performance of bryophytes in sunflecks (Glime, 2007), measurements are almost lacking. The only paper dealing with photosynthetic induction dynamics published so far revealed that two alpine mosses reached 90% of net photosynthetic capacity (Amax) within 3 min (Cui et al, 2009), whereas tracheophytes need usually 7-40 min (Naumburg & Elsworth, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…1; Table 2, Table S4 in the ESM). The reason for the similar LSPs of the two groups of bryophytes in our study is that they grow in similar environments and become acclimated to the shaded understory environment (Cui et al 2008;Rascher et al 2011). The higher photosynthetic capacity of erect bryophytes is due to their higher chloroplast pigment concentrations (Chl mass , Chl area , Carmass and Car area ), which enhance their ability to harvest the Table 2 Comparisons of functional trait levels [mean ± SE, range and variance (fold) of species means] between the two groups of bryophytes (p values for comparisons are shown) collected from the old-growth fir forest of Dagu Glacier Park There were 16 prostrate (P) and 12 erect (E) bryophytes, and n = 4 for each bryophyte…”
Section: Discussionsupporting
confidence: 56%
“…Very often only maximum quantum efficiency of PSII (F^/F^) has been used to characterize the photochemical performance of PSII in bryophyte tissues (Robinson et al, 2000;Proctor, 2003;Cui et al, 2009;Granath et al, 2009;Laine et al, 2011). However, the present study showed that other fluorescence parameters might be also useful in characterizing various aspects of photochemistry in bryophytes in field conditions, as there was no general linear relationship between them and FjF^.…”
Section: Discussioncontrasting
confidence: 54%
“…Recently chlorophyll fluorescence analysis has been used to study photosynthetic response to variability of light and moisture (Cui et al, 2009;Hájek et al, 2009), nitrogen deposition (Granath et al, 2009), growth rate (Laine et al, 2011), as well as salinity tolerance (Garbary et al, 2008;Bates et al, 2009). So far, fluorescence measurements have not been performed in natural habitats with several bryophyte species differing in putative adaptation strategies.…”
Section: Introductionmentioning
confidence: 99%